Sosialisasi Ragam Profesi dan Peran Aparat Penegak Keadilan di Indonesia - Lewiandy; Puji, Janice Arivi; Tanujaya, Natania Kayla (AL-SULTHANIYAH, 2026)
This Community Service Program (PKM) aims to enhance legal awareness and understanding among high school students of Provinsi DKI Jakarta through socialization activities introducing various legal professions and the roles of law enforcement officers in Indonesia. The program employed an interactive socialization method involving presentations, discussions, and Q&A sessions. The results indicate an improvement in students’ knowledge of the legal system and a growing interest in legal professions. Referring to Soerjono Soekanto’s Theory of Legal Awareness, this activity contributes to strengthening the two initial indicators of legal awareness—legal knowledge and legal understanding—which may foster positive legal attitudes and behavior in the future. Thus, this PKM serves as a strategic initiative to cultivate a legal culture among the younger generation.